The Effect of Developing and Implementing Health Education and Nutrition Training Program on Self-Management Practices among Patients with Iron Deficiency Anemia, Alexandria Main University Hospital, Egypt - Ahmed, Heba Abdel Mowla; Aljaber, Nadia Yasein; Aziz Ahmed, Eman Abdel; Gamal Ali, Lobna Mohamed (International Journal of Innovative Research in Medical Science, 2018)
Iron deficiency anemia (IDA) is most common nutritional deficiency disorder in Egypt and remains a formidable health challenge. Females in the reproductive period are prone to develop iron deficiency. Iron deficiency leads to many non-hematological disturbances which include growth and development, depressed immune function; reduces physical work capacity; decreases the cognitive function. Many researches consistently demonstrate that many patients with iron deficiency anemia do not have a solid understanding of basic information about their condition - how it is diagnosed, iron deficiency anemia high risk population, causes of iron deficiency anemia, the purpose and potential side effects of iron deficiency anemia medications, safety concerns, the risks and potential consequences of iron deficiency anemia. Patient education is an important component of quality care and is considered to be a therapeutic outcome for patients with iron deficiency anemia. Aim: the present study was aimed to: assess the effect of developing and implementing health education and nutrition training program on self-management practices among patients with iron deficiency anemia. Method: A cross-section in design conducted was conducted by using a self-designed standardized pretested questionnaire. IDA educational program was implemented and after 3 months post- test and Hb level were measured. Results: 91% women and 9 % male were surveyed for Iron Deficiency Anemia educational program. 56.0% of women had a poor knowledge of causes of IDA. There was a statistical significant differences between the pre-test and post-test of total score of patients’ knowledge (t= 63.848 P= 0.000). , there was highly statistically significant differences between pre/post program implementation in hemoglobin level (P < 0.00). Conclusion: Awareness regarding IDA is directly linked with the educational and social status of a community and is found to be increasing with the passage of time with exploration and accessibility to media and health care facilities. Women of younger ages are more concern about their own health and much careful about their expected babies in terms of nutritional facts as compared to the elder ladies.